Pengembangan Laboratorium Virtual Berbasis Inkuiri Terbimbing Tema Benda Di Sekitar Untuk Menumbuhkan Minat Belajar Peserta Didik Kelas VIII - Diyah Nadiyah; Suroso Mukti Leksono; Vica Dian Aprelia Resti (PendIPA Journal of Science Education, 2022)
At the junior hight school level in carrying out the science learning process, the teacher only applies the lecture method which only provides theory and does not carry put pratical so that students alack interest in learning. This result in the low active participation of students in learning activities and learning outcomes are less satisfactory. As an alternative to overcome partical problems and foster interest in learning, a virtual laboratory based on guided inquiry was developed with the theme of objects around us. The virtual laboratory is validated by experts, namely material experts, media and pratitioners to obtain validity data used in the learning process. The research method used is Research and Development  with reference to the development model of Thiagarajan (1974) which was modified in 3 stage. The instruments used are interview sheets and validation sheets. The results of the validity level of guided inquiry-based virtual laboratory with the theme of objects around us obtainded an average value of 92,67% with the ‘very valid’.  Based on this assessment, a guided inquiry-based virtual laboratory with the theme of objects around us in fostering interest in learning for students can be applied in learning activities.